Notes on the milliped Pleuroloma flavipes (Polydesmida: Xystodesmidae) in Wisconsin - (:unkn) unknown (My University, 1996)
The milliped Pleuroloma flavipes Rafinesque 1820 is one of the more widespread and better known North American millipeds. During the course of recent studies in Wisconsin, we have had opportunities to examine museum specimens and make field observations of this species. In this note, we report new locality records, discuss observations of mass aggregations, describe a color variation, and illustrate an individual with developmental abnormalities.
Keywords: millipede; Pleuroloma flavipes; Polydesmida; Xystodesmidae; Wisconsin